Induction of heat shock protein HSPA6 (HSP70B′) upon HSP90 inhibition in cancer cell lines. Issue 13 (7th May 2015) - Kuballa, Petric; Baumann, Anna-Lena; Mayer, Klaus; Bär, Ute; Burtscher, Helmut; Brinkmann, Ulrich
Abstract : Genome‐wide transcript profiling to elucidate responses to HSP90 inhibition revealed strong induction of HSPA6 in MCF‐7 cells treated with 17‐AAG. Time‐ and dose dependent induction of HSPA6 (confirmed by qPCR and Western Blots) occurred also upon treatment with Radicicol, another HSP90 inhibitor. HSPA6 was not detectable in untreated cells or cells treated with toxins that do not inhibit HSP90, or upon applying oxidative stress. Thus, HSPA6 induction is not a general response to cytotoxic insults. Modulation of HSPA6 levels by siRNA‐mediated inhibition or recombinant expression did not influence 17‐AAG mediated cell death. HSPA6 induction as a consequence of HSP90 inhibition occurs in various (but not all) cell lines and may be a more specific marker for HSP90 inhibition than induction of other HSP70 proteins. Abstract : HSP90 inhibition induces HSPA6. HSPA6 induction in cancer cells indicates exposure to geldanamycin. HSF activity is not sufficient to fully explain HSPA6 regulation.